What determines the holding of association meetings in a global context? - Carvalho, Pedro (2019)
This article aims to understand the determinants influencing the number of association meetings held in countries worldwide and which may be controlled by their economic agents and policymakers. For this purpose, we use a dynamic panel model with data provided by the Data World Bank, the World Travel & Tourism Council, and the International Congress and Convention Association, in a time series of 8 years. The results reveal the importance of the experiences obtained by the tourists in previous meetings, as well as the countries’ need to implement measures to stimulate the dynamism of economic activity and political stability.